2016
DOI: 10.4212/cjhp.v69i2.1549
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacy Activities: We Know What to Do, but for Whom Should We Do It?

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Clinical activities in pharmacies involve pharmacists providing patient care to optimize medication therapy and to promote health, wellness, and disease prevention [1]. Among such activities are the identification, prevention, and resolution of drug-related problems (DRPs) [2,3]. A DRP is defined as an event or circumstance involving drug therapy that actually or potentially interferes with desired health outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical activities in pharmacies involve pharmacists providing patient care to optimize medication therapy and to promote health, wellness, and disease prevention [1]. Among such activities are the identification, prevention, and resolution of drug-related problems (DRPs) [2,3]. A DRP is defined as an event or circumstance involving drug therapy that actually or potentially interferes with desired health outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Clinical pharmacists can prioritize the care they provide and add value by making evidence-based pharmacotherapy interventions for patients with priority diseases. 4 Two randomized controlled trials showed that hospital pharmacists providing comprehensive proactive clinical care and identifying and resolving drug therapy problems (DTPs) for patients with priority disease states can improve the overall quality of drug therapy, thereby reducing emergency department visits, hospital visits, drug-related readmissions, hospital readmissions, and total cost of care. 5,6 Most importantly, these trials confirmed that pharmacist-resolved DTPs are a useful process measure in continuous quality improvement projects to evaluate clinical pharmacy services, and represent an acceptable surrogate marker for predicting clinical and economic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the patient to pharmacist ratio for patients with renal disease can impede a pharmacist from identifying and resolving all DTPs for all patients in a timely manner. Taking into account the complexity of renal patients in terms of their medical conditions and medication regimens, the renal pharmacist's efforts need to be focused on performing priority activities that will provide the greatest value to the patient and the health system . Quality indicators are commonly used in health care to track performance and identify areas for improvement and manage improvement activities .…”
Section: Introductionmentioning
confidence: 99%
“…Quality indicators are commonly used in health care to track performance and identify areas for improvement and manage improvement activities . They can also assist pharmacists in identifying priority patients for whom they should provide interventions …”
Section: Introductionmentioning
confidence: 99%